Case reportAcute coronary syndrome in a 100-year-old woman treated successfully with primary percutaneous coronary angioplasty - Karwowski, Jarosław; Bęćkowski, Maciej; Szwed, Hanna; Ciszewski, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We present a case of a 100-year-old woman living alone with ST-elevation myocardial infarction acute coronary syndrome of the infero-lateral wall treated with percutaneous coronary intervention. Coronary angiography revealed critical 99% stenosis in the marginal branch of the circumflex artery and insignificant lesions in other arteries. Two bare metal stents were implanted successfully in the same session. The patient was discharged home in good general condition, able to live and function independently.